ФРАЗЕОЛОГИЗМЛЕР – ЭТНОЛИНГВИСТИКА ҲӘМ ЛИНГВОМӘДЕНИЯТТАНЫЎДЫҢ БАСЛЫ ИЗЕРТЛЕЎ БАҒДАРЫ - Зайрова, Қ. (SCIENCE and SOCIETY, 2024)
The article deals with idioms from the vocabulary of the Karakalpak language, which reflect the fate of the people that has passed through time, with its rich heritage and unique expressions.
Keywords: linguistics; phraseology; ethnolinguistics; cultural linguistics; myth; paremiology; ethnicity; ethnolexicon; culture